Experimental investigation and performance analysis of nano enhanced phase change material based photovoltaic thermal system / Mohammed Moinul Islam - Mohammed Moinul , Islam (2022)
Photovoltaic systems suffer from a paradoxical problem that they need sun light for their operation, but their performance abates with increasing temperature. Commercially available photovoltaic modules (PV) converts less than 20% of the approaching solar energy into power, the rest being dissipated as heat which further affects the conversion efficiency of the module by augmenting its temperature. Co-generation of electricity and heat from a single module, known as photovoltaic thermal (PVT) module, offers a hands-on solution to this problem. However, the major shortcoming with PVT collectors consists in its inefficacy in heat removal and storage of mostly employed heat transfer fluids (HTF) – air and water. As such both fluids suffer from low thermal conductivity and poor specific heat, PVT/air and PVT/water collectors cannot achieve a sustained low cell temperature with considerable electrical efficiency. Phase change materials (PCM) having very good latent heat capacity can be used for thermal control of these collectors, but their poor thermal properties turns out to be barrier in effective heat removal. Hence, incorporation of highly conductive nanoparticles such as carbon nanotube may offer a credible solution to this problem. In the present research, multi-walled carbon nanotube (MWNT) has been used to develop a very new nano enhanced PCM (NePCM) and thus apply this composite material in PVT systems to achieve better thermal control through enhanced thermal properties. Four NePCMs with concentration of functionalized MWNT (f-CNT) ranging from 0.25%wt to 0.01%wt have been synthesized. Detailed characterization of these nano composite materials has been performed by field emission scanning electron microscopy (FESEM), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and Fourier transform infrared (FTIR) spectroscopy and thermal conductivity analysis. With a 3% increase in heat storage capacity and 15% upsurge in thermal conductivity NePCM RT44HC-0.01%fCNT has been confirmed as the best nano composite material for photovoltaic thermal application. Hence, this NePCM has been integrated with a commercially popular parallel-flow PVT and real-time performance of this PVT-NePCM system has been investigated in the outdoor conditions of Kuala Lumpur, Malaysia. To observe whether PVT-NePCM system perform better than other conventional PV and PVT systems four other panels, viz., a reference PV, a PVT with same collector design, a PV-PCM and a PVT-PCM system have been erected in line with the novel PVT-NePCM system to ensure the same ambience. All operating and ambient parameters (different temperatures, solar irradiance, HTF flow rate, wind speed, etc.) have been measured and recorded concurrently by digital data acquisition system from June to September 2019. Thermal performance has been analyzed from both energy and exergy viewpoints. Results show that PVT-NePCM system achieved, at least, 4oC lower cell temperature than other systems and it operates with an energy efficiency of 85.3% and exergy efficiency of 13%. Moreover, PVT-NePCM system extends the cooling period of the solar cells by 37.5% as compared with PVT only system. Extensive application of such system can abate dependence on fossil fuels and help to improve the environment as well.